Sustainable development for soya production based on the field research carried out at the Variety Assessment Experimental Station of Głubczyce in the years 2015-2017 - Marta Bednarczyk; Izabella Pisarek (Economic and Environmental Studies (E&ES), 2019)
The aim of this research was to determine the impact of various nitrogen fertilization systems in soya cultivation on quality and quantity of crop, as well as to examine the economic aspects of sustainable farming. The study was based on research carried out in the Variety Assessment Research Station of Głubczyce (years: 2015-2017). The soybean, protein and fat of four soya varieties (Glycine max (L.)Merrill) non-GMO (Augusta, Mavka, Aligator, Lissabon) were compared, using varying doses of N/ha (0, 30 and 60 kg). The cost effectiveness of the various fertilization doses was also determined. The soybean yields of the different soya varieties differed significantly, which indicates the existence of interdependence between weather conditions during growth and both quantity and quality. Fertilizing with 30 kg N/ha was the optimal rate both in terms of quality and quantity of the yield, as well as economically. The varieties of 'Aligator' and 'Lissabon' proved the best suited to the climate and environment of Głubczyce region, regarding significant LSD coefficients.
Keywords: Q01; Q19; 330; sustainable development; soya; non-GMO; nitrogen fertilizer